2019
DOI: 10.1097/cm9.0000000000000079
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chronic kidney disease staging with different estimated glomerular filtration rate equations in Chinese centenarians

Abstract: Background:Accurate estimation of the glomerular filtration rate (GFR) and staging of chronic kidney disease (CKD) are important. Currently, there is no research on the differences in several estimated GFR equations for staging CKD in a large sample of centenarians. Thus, this study aimed to investigate the differences in CKD staging with the most commonly used equations and to analyze sources of discrepancy.Methods:A total of 966 centenarians were enrolled in this study from June 2014 to December 2016 in Hain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…We found that UA level was an independent predictor of changes in serum creatinine; FT3 and FPG were predictors of iGFR, consistent with the literature. 25–30 This is further confirmed our assumption that SRCs may be a manifestation of declined renal function in T2D (mean eGFR: 65.02±22.71 mL/min*1.73m 2 ), but the cyst volume parameter in the current study (as shown in Table 1 ) did not significantly alter the kidney function. We substantiate that besides the number, location and type of renal cysts, the volume of renal cysts may not be the ideal or exclusive indicator to predict the effect of renal cysts on kidney filtration function, unlike previous reports.…”
Section: Discussionsupporting
confidence: 90%
“…We found that UA level was an independent predictor of changes in serum creatinine; FT3 and FPG were predictors of iGFR, consistent with the literature. 25–30 This is further confirmed our assumption that SRCs may be a manifestation of declined renal function in T2D (mean eGFR: 65.02±22.71 mL/min*1.73m 2 ), but the cyst volume parameter in the current study (as shown in Table 1 ) did not significantly alter the kidney function. We substantiate that besides the number, location and type of renal cysts, the volume of renal cysts may not be the ideal or exclusive indicator to predict the effect of renal cysts on kidney filtration function, unlike previous reports.…”
Section: Discussionsupporting
confidence: 90%
“…Clinically, the increase in serum creatinine (Scr) indicates damage to renal function as well. 24 The level of cysteine protease inhibitor C (Cys-C) is determined by glomerular filtration, not affected by any external factors (gender, age, diet). 25 Slightly elevated of Cys-C level may indicate renal insufficiency, but its low level can also happen in early kidney damage.…”
Section: Introductionmentioning
confidence: 99%